PENERAPAN ALUR BAGJA DALAM SUPERVISI KLINIS UNTUK MENINGKATKAN PROFESIONALISME GURU SD NEGERI INPRES SEREH KAB.JAYAPURA - Widiastuti, Tipuk; Dwikurnianingsih, Yari; Sanoto, Herry (Consilium: Education and Counseling Journal, 2025)
This study aims to apply the BAGJA framework in clinical supervision to enhance teacher professionalism at SD Negeri Inpres Sereh, Jayapura Regency. The BAGJA framework, which consists of the stages of Creating Questions, Learning Lessons, Exploring Dreams, Outlining Plans, and Managing Execution, is implemented as a systematic method in clinical supervision to provide targeted support to teachers. This research uses a qualitative method, with data collection techniques including observation, interviews, and documentation. Data were collected from teachers involved in clinical supervision, the principal, and supervisors. The results of the study indicate that the implementation of the BAGJA framework significantly supports the improvement of teacher professionalism, especially in the aspects of planning, implementation, and evaluation of learning. Teachers who participated in supervision using the BAGJA framework showed improvements in teaching methods and self-reflection skills. The conclusion of this study states that clinical supervision based on the BAGJA framework is effective in enhancing teacher professionalism and contributes positively to the quality of education in elementary schools.